At-Taʻlīm wa at-Taʻallum as-Siyāqī wa Mauqiʻ al-Jazīrah li Taʻlīm al-ʻArabiyyah - Fina Aunul Kafi (INAIFAS PRESS, 2021)
Students need contextual Arabic learning to improve Arabic language competence that is relevant to the target language environment through using of internet sites as alternative teaching materials such as those contained in Learning Aljazeera site. This article aimed to discuss Learning Aljazeera site as an alternative teaching material in Arabic learning based on contextual teaching and learning. Researcher used contain analysis method to discuss and analyze the site. From the data analysis, it showed that the material on the site consisted of media language and general language that prioritized fahm al-masmūʻ and fahm al-maqrūʻ through various topics based on student level in addition to basic materials such as phonology and syntax. Learning Aljazeera sites can support the needs of learning Arabic today and can be used for contextual learning purposes in Arabic lessons.